The arctic patrol mystery - Dixon, Franklin W. (New York Grosset & Dunlap, 1997)
While searching in Iceland for a missing sailor sought by an insurance company, the teen-age detective brothers uncover a plot threatening the life of a United States astronaut and the secrets of NASA's moon project.
Keywords: Detective and mystery stories -- Juvenile fiction; Hardy Boys (Fictitious characters) -- Fiction; Mystery fiction